Overview of Risk Factors for the Incidence of Malnutrition there are Toddlers in Tamalanrea District, Makassar City in 2019 - Asrul Ilyas; Andi Sitti Rahma; Dewi Setiawati (Jurnal Multidisiplin Madani, 2023)
Poor nutrition is the condition of a person with below-average nutrition. This is a form of the process of chronic malnutrition. The purpose of the study: to determine the description of risk factors for malnutrition in children under five, including socioeconomic status, maternal education, frequency of infectious diseases, maternal knowledge, birth weight, and exclusive breastfeeding.  This study is a descriptive study with a cross sectional design. The sample of this study used purposive sampling method.  Atotal of 70 samples in this study,  including 45 malnourished children under five and 25 not malnourished in Tamalanrea sub-district, Makassar City. Results of the  study: malnutrition group as much as 84.4% were in low socioeconomic status, 62.2% came from the lowest education level n 73.4% were not exclusively breastfed, 66.7% had a history of low birth weight,  66.7% were born to mothers with a low level of  maternal knowledge, and 60% had a history of high infectious diseases.  Conclusions: socioeconomic level, mother's education level, mother's knowledge, birth weight of malnourished children tend to be lower than children who are not malnourished. Children with poor nutrition tend not to get exclusive breastfeeding, and the frequency of suffering from infectious diseases is more frequent than children who are not malnourished